Ferrous Iron Under Oxygen‐Rich Conditions in the Deep Mantle. Issue 3 (14th February 2019) - Boulard, E.; Harmand, M.; Guyot, F.; Lelong, G.; Morard, G.; Cabaret, D.; Boccato, S.; Rosa, A. D.; Briggs, R.; Pascarelli, S.; Fiquet, G.
Abstract: Recent experiments have demonstrated the existence of previously unknown iron oxides at high pressure and temperature including newly discovered pyrite‐type FeO2 and FeO2 Hx phases stable at deep terrestrial lower mantle pressures and temperatures. In the present study, we probed the iron oxidation state in high‐pressure transformation products of Fe 3+ OOH goethite by in situ X‐ray absorption spectroscopy in laser‐heated diamond‐anvil cell. At pressures and temperatures of 91 GPa and 1, 500–2, 350 K, respectively, that is, in the previously reported stability field of FeO2 Hx, a measured shift of −3.3 ± 0.1 eV of the Fe K‐edge demonstrates that iron has turned from Fe 3+ to Fe 2+ . We interpret this reductive valence change of iron by a concomitant oxidation of oxygen atoms from O 2− to O −, in agreement with previous suggestions based on the structures of pyrite‐type FeO2 and FeO2 Hx phases. Such peculiar chemistry could drastically change our view of crystal chemistry in deep planetary interiors. Plain Language Summary: Iron oxides are important end‐members of the complex materials that constitute the Earth's interior. Among them, FeO and Fe2 O3 have long been considered as the main end‐members of the ferrous (Fe 2+ ) and ferric (Fe 3+ ) states of iron, respectively. All geochemical models assume that high oxygen concentrations are systematically associated to the formation of ferric iron in minerals. The recent discovery of O2 2− peroxide ions in a phase of chemical formula FeO2 Hx stable under high‐pressure and high‐temperature conditions challenges this general concept. However, up to now, the valences of iron and oxygen in FeO2 Hx have only been indirectly inferred from a structural analogy with pyrite FeS2 . Here we compressed goethite (FeOOH), an Fe 3+ ‐bearing mineral, at lower mantle pressure and temperature conditions by using laser‐heated diamond‐anvil cells, and we probed the iron oxidation state upon transformation of FeOOH in the pressure–temperature stability field of FeO2 Hx using in situ X‐ray absorption spectroscopy. The data demonstrate that upon this transformation iron has transformed into ferrous Fe 2+ . Such reduced iron despite high oxygen concentrations suggests that our current views of oxidized and reduced species in the lower mantle of the Earth should be reconsidered. Key Points: Ferrous iron is evidenced in coexistence with high oxygen concentration modifying our understanding of deep Earth geochemistry In situ X‐ray absorption spectroscopy shows the reduction of iron into Fe 2+ when FeOOH transforms into the pyrite‐structured phase FeO2 Hx Subduction of FeOOH‐type hydrated iron oxides releases zero‐valent hydrogen (H2 ) instead of mono‐valent hydrogen (H2 O) in the lower mantle